2001
DOI: 10.1006/dbio.2001.0161
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-Independence of Limb Regeneration in Larval Xenopus laevis Is Correlated to the Level of fgf-2 mRNA Expression in Limb Tissues

Abstract: In both larval and adult urodele amphibians, limb blastema formation requires the presence of an adequate nerve supply. In previous research, we demonstrated that the hindlimb of early Xenopus laevis larvae formed a regeneration blastema even when denervated, while the denervated limb of late larvae did not. We hypothesized that the nerve-independence was due to the autonomous synthesis of a mitogenic neurotrophic-like factor by undifferentiated limb bud cells. In this paper, we demonstrate that fgf-2 mRNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 63 publications
3
27
1
Order By: Relevance
“…These factors are thought to target the wound epidermis and enable blastema maintenance. Nerve dependence has not been found for Xenopus at a stage when limbs do regenerate successfully (Filoni and Paglialunga, 1990;Cannata et al, 2001). In contrast, the regeneration of a hypomorphic spike in postmetamorphic animals does appear to be nerve dependent.…”
Section: )mentioning
confidence: 97%
“…These factors are thought to target the wound epidermis and enable blastema maintenance. Nerve dependence has not been found for Xenopus at a stage when limbs do regenerate successfully (Filoni and Paglialunga, 1990;Cannata et al, 2001). In contrast, the regeneration of a hypomorphic spike in postmetamorphic animals does appear to be nerve dependent.…”
Section: )mentioning
confidence: 97%
“…8 The nerve dependence of fetal wound healing has also been reported. In lamb fetal limb experiments, the presence of scarring was reported on the denervated side, whereas the skin was regenerated without scarring on the opposite enervated side.…”
Section: Nerve Dependencymentioning
confidence: 97%
“…Studies on Xenopus limb regeneration have shown that the early buds will regenerate without nerves, but the later buds do need them; otherwise the loss of regenerative ability occurs about two developmental stages earlier than usual [84]. The synthesis of FGF2 is found in early but not later mesenchyme, suggesting that FGFlike factors may underlie the neurotrophic effect [85].…”
Section: The Limbmentioning
confidence: 98%